The Influence of the PBL Model on Student Learning Motivation and Discipline Materials to Emulate the Prophet in High School - Mochamad Haikaladiya; Jaenal Abidin; Ferianto (al-Afkar, Journal For Islamic Studies, 2025)
This research consists of two variables, namely the habit of Duha prayer and religious character, so the aim of this research is to describe the results of the problem based learning model on students' learning motivation and discipline, as well as the influence of both in a correlational relationship. The population in this study was all students at SMAN 1 Jatisari, and the sample was 120 students. The research method used in this research is correlational research with a quantitative approach. This method was chosen to identify the relationship between problem based learning and student motivation and discipline. Data related to problem based learning experiences on students' learning motivation and discipline were collected using a questionnaire instrument, which was prepared using a Likert scale, data analysis techniques used descriptive and inferential analysis. The results of this research show that 9% of students are in the low category, 81% are in the medium category and 10% are in the high category, so it can be concluded that the average problem based learning model for students is in the medium category. Motivation and Discipline 9% in the low category, 79% in the medium category and 12% in the high category, so it can be concluded that the average Motivation and discipline is in the medium category. Based on the SPSS output in the Coefficientsa table, it is known that the significance value (sig.) is 0.000 < 0.05 so it can be concluded that H0 is rejected and Ha is accepted, which means that "There is an influence of the problem based learning model (X) on student motivation and discipline (Y ).” From the results it is known that the R Square value is 0.890. This value means that the influence of the Problem Based Learning Model (X) on Learning Motivation and Discipline (Y) is 89.0%, while 11.0% of Learning Motivation and Discipline (Y) is influenced by other variables that were not studied.